Women in Agriculture – An Analysis of Occupational Health Hazards Faced by them and Measures to Overcome it - Dr. Bhavana Singh (International Journal of Modern Agriculture, 2021)
Women in India are extensively involved in agriculture and other allied activities. She is considered as the backbone of agriculture, and does the most tedious and backbreaking tasks, but her hard work is mostly unpaid. More than 43% of women farm workers constitute the labour force in agriculture in developing countries. Rural women form one of the most important productive workforce, and are involved in agriculture and allied activities including crop production, livestock production, horticulture post harvesting etc. yet their services are ignored and unnoticed especially in the agriculture sector. Occupational health is an important part of a country’s economy because it relies on workers’ physical, emotional, and social wellbeing. Occupational health among agricultural women is a public health problem in India that requires urgent attention. In India, occupational health hazard being a public issue pose a threat to the women and need to be tackled soon. Women’s roles and positions in meeting the demands of agricultural production and growth are very influential and popular. Above all, she faces ignorance, financial pressures, a lack of sufficient educational services, sexual harassment, poor wages, and so on. Their importance in the agricultural sector is equal to that of men. As a result, farm women should be educated. This paper focusses on the trends in the womenâ€™s participation, occupational health hazards faced by them and measures to overcome